Pharmacokinetic profile of phenytoin in dried blood spot with high-performance liquid chromatography—photodiode array - Harahap, Yahdiana; Ng, Limeylia; Sunarsih, Sunarsih (Frontiers in Pharmacology, 2024)
Phenytoin is a first-line antiepileptic drug with narrow therapeutic range and follows non-linear pharmacokinetics. Pharmacokinetics of phenytoin have been studied in plasma matrix before, however, there were several disadvantages. This study aimed to obtain partial validation data of the analytical method and the pharmacokinetic profile of phenytoin in Dried Blood Spot (DBS) of six healthy subjects. DBS has the advantage of only requiring small sample volumes and could be transported more efficiently. Phenytoin along with carbamazepine as the chosen internal standard was analyzed with a reversed-phase high performance-liquid chromatography system and a photodiode array detector at 205 nm. The results of partial validation, which evaluated the linearity, within-run accuracy, and precision, were within the criteria acceptance range. The pharmacokinetic profile showed that average AUC0-t was 83.81±37.32 μg.hr/mL and AUC0-∞ was 83.65±38.89 μg.hr/mL with an average ratio of 93%. Previous study quantifying phenytoin in the plasma matrix found the average AUC0-t was 39.41±8.57 µg.hr/mL and AUC0-∞ was 42.94±9.55 µg.hr/mL. Despite the difference between parameters of phenytoin analyzed in DBS and plasma matrices, the pharmacokinetic profiles obtained from both matrices were similar indicated by comparable concentration-time curves, thus, proving that DBS matrix can be used interchangeably with the plasma matrix as a more comfortable and effective alternative to phenytoin quantification in blood.